Centro aberto: “requalificação” do centro de São Paulo e o conhecimento racional do urbanismo - Silva, Guilherme Corigliano (2019)
This study analyzes the Programa Centro Aberto, composed of urban interventions that aim to “regenerate” public spaces in downtown São Paulo. São Paulo-Urbanismo is the city’s agency responsible for coordinating the program, conceived through Gehl Architects’ consultancy engagement in 2013. With this in mind, we propose an analytical approach that seeks to comprehend the ways through which the rational knowledge of urban design composes and operates the “requalification” project led by the municipal government. For that, we analyzed qualitative interviews along with the technical team responsible for the program’s development. Starting from this issue, this study investigates how the relationships between the bureaucratic body and the political power inside the city’s administration